(untitled) (Medical Forum Monthly, 2024)
Objective: To study coagulation activation markers and anemia in chronic kidney Disease patients. Study Design: Comparative / cross sectional study. Place and Duration of Study: The study was conducted at the Pathology Department of Hayatabad Medical Complex Peshawar (HMC) from Feb 2017 to May 2018. Materials and Methods: In this study total of 100 patients of chronic kidney disease (CKD) were included and 50 individuals were taken as a control group. All patients of CKD were evaluated for anemia and hemostatic marker, ie D-dimer, PT and APTT. Results: A total of 95 (95%) of the patients were anemic. Mean Hemoglobin (Hb) level was 9.625±1.253 g/dl. Significantly low as compared with the control group. In 75% of CKD patients, D-dimer levels were elevated. Mean D-dimer level was in the range of 500-1000ng/µl, significantly elevated as compared to control group. 3 out of 100 CKD patients showed prolonged PT and 4 out of CKD patients showed prolonged APTT. Mean PT and APTT were 11.52± 1.562 seconds and 28.562±1.562 respectively. 5 out 100 CKD patients showed thrombocytopenia. Mean platelets counts were 150.562±10.562×1/µl. Similarly 6 out of 100 CKD patients showed prolonged BT mean BT as 12.562±1.265 minutes. Conclusion: The study concluded that chronic kidney disease patients are significantly associated with anemia and hemostatic abnormality. Therefor proper attention should be given to these patients, as anemia and coagulation abnormality may lead to severe complications and increase morbidity and mortality from the disease. These patients should be properly managed regarding anemia and hemostatic abnormality, to improve their life style. Further work up and assessment is necessary in this regard to prevent any thromboembolic phenomenon.